Comparative analysis of European and Kazakh academic mobility - Azmukhanova, А. M.; Baspak, Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
The study of the international experience of the Kazakhstani higher education program, as well as the program of academic mobility in the context of globalization is а particular importance today. This article analyzes the logic of Kazakhstan’s entry into the top 30 developed countries of the world, defined in the Strategy “Kazakhstan-2050: the New Political Course of the Developed State”. Based on the European experience, some of the problems and challenges facing a modern academic mobility program will be analyzed. A comparative study revealed inconsistencies at the academic stages of domestic and foreign universities in ECTS credits, proper organization of funding in terms of mobility, the work of a special group or organization for the adaptation of students, and comprehensive support. Academic mobility is considered in the context of several issues as a new tool for the development of the European educational space.